Employee Development as Social and Economic Precondition of Russia’s Transition to Innovation-based Type of Development - I. G. Kuftyrev (MGIMO University Press, 2013)
The article’s focus is the employee development as an economic category viewed simultaneously as a result and a precondition of becoming innovation-based economy. A quantitative criterion based on the economies of working time and defining social and economic efficiency of innovations is introduced. The author suggests that the investments into the human capital is a critical factor of employee development and a milestone of a new paradigm of partnership between an employer and an employee